Long-term clinical outcomes in patients with hypertrophic cardiomyopathy versus hypertensive heart disease. - Park, William D.; Chrusciel, Timothy; Verma, Divya R.; Benjamin, Mina M. (Baylor University Medical Center Proceedings, 2024)
Background: For most patients with hypertrophic cardiomyopathy (HCM), the clinical course is considered relatively benign, similar to hypertensive heart disease (HHD). We compared the long-term outcomes in patients with HCM versus HHD from a large healthcare system database. Methods: Data from SSM Virtual Data Warehouse were used to identify patients with a new diagnosis of either HCM or HHD who followed up in our system for at least 6 months. HCM patients were matched 1:1 to HHD patients based on age, sex, and race. Outcomes examined included heart failure (HF) admission, ventricular tachyarrhythmia (ventricular fibrillation or sustained ventricular tachycardia), and need for pacemaker or defibrillator implantation. We identified 1904 HCM patients along with HHD controls. Results: After adjusting for demographic characteristics and relevant comorbidities, HCM had higher odds of HF admission (odds ratio [OR]: 1.73, 95% confidence interval [CI]: 1.43–2.10), ventricular tachyarrhythmias (OR: 2.31, CI: 1.60–3.33), pacemaker implantation (OR: 2.14, CI: 1.29–3.57), and defibrillator implantation (OR: 3.77, CI: 1.82–7.83). Survival analysis confirmed the difference in outcomes early on from the time of diagnosis. Conclusion: In this retrospective study from a large healthcare system database, HCM patients had significantly higher incidences of HF admission, ventricular tachyarrhythmias, and pacemaker or defibrillator implantation compared to HHD patients.